Design and implementation of agent interaction mechanisms for emotionally intelligent tutoring systems - Petrovica Sintija; Anohina-Naumeca Alla (Applied Computer Systems, 2012)
Modern intelligent systems are built from intelligent agents, but usually agent interaction mechanisms are described at the general level omitting design and implementation details. The paper presents aspects of practical implementation of agent interaction mechanisms in JADE platform on the basis of the set of agents for modelling student’s emotions in intelligent tutoring systems. The concepts of an intelligent and affective tutoring system, agent, and agent interaction are explained, as well.